June Mickle : one woman's life in the foothills and mountains of western Canada - Calvert, Katherine M., 1947- (Rocky Mountain Books Ltd., 2015)
"An inspiring biography of an adventurous woman who grew up on a small ranch in southern Alberta during the Depression. In spite of many hardships, she and her family became some of the most important mountain outfitters in the Banff and Yoho national parks. June's strength of character was forged by living in the wilderness west of Turner Valley as a young girl with her mother and her stepfather, Tip Johnson, a renowned cowboy and horse trainer. She learned early to live in harmony with her environment and became a strongly determined woman capable of meeting the challenges of being an artist, horseback guide, businesswoman, wife and mother. As the only child of a single mother, June saw early years that were were marked by loneliness but also by close family ties that defined how she would chart her adult life. As well, it led to a love of horses that played an essential part of her life right up until her death at the age of 91. Her life with Bert Mickle, the son of a long-established ranching family, was unconventional. It is a love story of two people coping with family struggles and a precarious existence that had tremendous rewards and hardships. June's strength of character held her family together despite unforeseen tragedies."--